Prevalence and Risk Factors of Low Back Pain and Shoulder Pain among Mechanics at Tyre Service Center at Taiping, Perak - Mazlina Kamarudzaman; Mohd Zaki, Nurul Elyna Asyiqen; Abdol Rahman, Mohd Nasrull (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Symptoms and disorders of the musculoskeletal system (MSDs) are the most common reasons for absent from work in Malaysia. Physical work load and more specifically manual materials handling is generally considered to be an occupational risk factor for low back and shoulder complaints. A recent review of epidemiological literature revealed that pushing and pulling assessment is suggested to be a risk factor of musculoskeletal complaint. In light of that, this paper combines results of several studies to present an approach for evaluating not only the exerted hand forces, but also the low back and shoulder load during pushing and pulling in practice. This study was conducted in Taiping, Perak. Data was collected using a structure questionnaire which is Nordic Musculoskeletal Questionnaire (NMQ). A cross sectional questionnaire survey was carried out among 39 workers from several workshop with mainly pushing and pulling assessment. The NMQ was used to assess the exposure to pushing and pulling and other physical risk factors for low back and shoulder pain. Psychosocial factors at work were also assessed. The mean age of the respondents were 30 years. In this study, it was found that 68% automobile mechanics had been troubled with musculoskeletal symptoms. RAPP analysis shows that 55% automobile mechanics are in medium risk level to develop musculoskeletal symptoms due to extreme posture and hand grip. Initial and sustained exerted forces were not highly correlated with the mechanical load at the low back and shoulders within the studied range of the exerted forces. A clear association between pushing and pulling and musculoskeletal disorder may become apparent in several definitions of pain. Therefore, the objective of the present study was to examine the association between the Risk Assessment of Pushing and Pulling (RAPP) and Nordic musculoskeletal questionnaire (NMQ) among mechanics.